Thioridazine induces major changes in global gene expression and cell wall composition in methicillin-resistant Staphylococcus aureus USA300. - Mette Thorsing (Public Library of Science (PLoS), 2013)
Subinhibitory concentrations of the neuroleptic drug thioridazine (TDZ) are well-known to enhance the killing of methicillin-resistant Staphylococcus aureus (MRSA) by β-lactam antibiotics, however, the mechanism underlying the synergy between TDZ and β-lactams is not fully understood. In the present study, we have examined the effect of a subinhibitory concentration of TDZ on antimicrobial resistance, the global transcriptome, and the cell wall composition of MRSA USA300. We show that TDZ is able to sensitize the bacteria to several classes of antimicrobials targeting the late stages of peptidoglycan (PGN) synthesis. Furthermore, our microarray analysis demonstrates that TDZ modulates the expression of genes encoding membrane and surface proteins, transporters, and enzymes involved in amino acid biosynthesis. Interestingly, resemblance between the transcriptional profile of TDZ treatment and the transcriptomic response of S. aureus to known inhibitors of cell wall synthesis suggests that TDZ disturbs PGN biosynthesis at a stage that precedes transpeptidation by penicillin-binding proteins (PBPs). In support of this notion, dramatic changes in the muropeptide profile of USA300 were observed following growth in the presence of TDZ, indicating that TDZ can interfere with the formation of the pentaglycine branches. Strikingly, the addition of glycine to the growth medium relieved the effect of TDZ on the muropeptide profile. Furthermore, exogenous glycine offered a modest protective effect against TDZ-induced β-lactam sensitivity. We propose that TDZ exposure leads to a shortage of intracellular amino acids, including glycine, which is required for the production of normal PGN precursors with pentaglycine branches, the correct substrate of S. aureus PBPs. Collectively, this work demonstrates that TDZ has a major impact on the cell wall biosynthesis pathway in S. aureus and provides new insights into how MRSA may be sensitized towards β-lactam antibiotics.